Regression based quasi-experimental approach when randomisation is not an option: interrupted time series analysis. (9th June 2015) - Kontopantelis, Evangelos; Doran, Tim; Springate, David A; Buchan, Iain; Reeves, David
Abstract : Interrupted time series analysis is a quasi-experimental design that can evaluate an intervention effect, using longitudinal data. The advantages, disadvantages, and underlying assumptions of various modelling approaches are discussed using published examples